Batteries: Twisting Carbon Nanotube Fibers for Both Wire‐Shaped Micro‐Supercapacitor and Micro‐Battery (Adv. Mater. 8/2013). (15th February 2013) - Ren, Jing; Li, Li; Chen, Chen; Chen, Xuli; Cai, Zhenbo; Qiu, Longbin; Wang, Yonggang; Zhu, Xingrong; Peng, Huisheng
<x xml:space="preserve">Abstract</x> Aligned carbon nanotube/MnO2 composite fibers are twisted to produce wire‐shaped supercapacitors and lithium ion batteries with high performances. The energy densities achieve 92.84 and 35.74 mWh/cm3 while the power densities reach 3.87 and 2.43 W/cm3 during the charge and discharge process, respectively. The wire structure enables many unique applications, e.g., being woven into electronic textiles. More details can be found in the article by Huisheng Peng, Yonggang Wang and co‐workers on page 1155. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>